Gestión administrativa y su incidencia en la rentabilidad de la empresa pública de producción y desarrollo estratégico de la UTEQ - PRODEUTEQ del Cantón Quevedo periodo 2020-2021 - Arcalle Cervantes, Priscila Johanna (2023)
Administrative management is a fundamental role in the activities of a company. The present research work will be carried out in the Public Company of Production and Strategic Development of the UTEQ - PRODEUTEQ, located in the Quevedo canton, whose mission is to provide services to the general public, its productive areas considered business programs addressed from the following: ESCUTEQ, CECAPRO, SOLUTEQ AND PROCOMBISE, the same ones that present some problems such as the breach of commitments acquired by the scarce technical personnel in the production area. The main objective of the research will be to evaluate the administrative management and its impact on profitability, which will allow identifying if there are any errors within the internal administrative processes, to improve and thus be able to provide quality care, through the efficient use of resources. Available the methodology used will be explanatory and descriptive, quantitative and qualitative methods will be used, which will allow the analysis of the study problem to obtain the conclusions of the investigation. The information collection process will be carried out through the use of techniques such as reading, observation, and survey, directed at the administrative personnel involved in administrative management and resource management, to obtain relevant information. Determining a level of efficiency and effectiveness with low risk within the administrative and financial management processes of the public company.